860 Variable Sleep Apnea Syndromes Complicated by Neurosurgeries in a Patient with Chiari Malformation Type 1. (3rd May 2021) - Ananth, Ashwin; Fares, Elie; Sagalow, Emily; Nemargamulla, Swetha; Fast, Zhanna
Abstract: Introduction: Chiari malformations (CM) are congenital conditions defined by craniocervical junction anatomic anomalies with downward displacement of cerebellar structures. Sleep-disordered breathing (SDB) including obstructive sleep apnea (OSA), bradypnea, central sleep apnea (CSA), and hypoventilation are described in CM patients. Report of case(s): 31-year-old male with history of CM type 1 presented to the sleep medicine clinic for management of OSA and CSA diagnosed at age 16. PSG showed an apnea-hypopnea index (AHI) of 14.2, RDI of 29, and no central events. He was started on auto-CPAP with pressures of 5–20 with subsequent visits showing high residual AHI. A subsequent CPAP-titration study resulted in a pressure of 16cm H2O yielding AHI of 0. CPAP pressure was fixed, but a high residual AHI persisted despite excellent compliance. A split-night study resulted in a BiPAP prescription, for which a titration study noted PAP-emergent CSA. He was started on auto Bilevel with IPAP of 30, EPAP of 8 and backup rate of 12bpm. Despite treatment, elevated AHI persisted so he was switched to adaptive servo-ventilation (ASV) with nightly oxygen blended in resulting in controlled complex sleep apnea. SDB management was complicated by multiple neurosurgical decompressions. During the most recent procedure, he was found to have syringomyelia, syringobulbia, and a mass at the brainstem. Surgery, including placement of a 4th ventricle stent and mass excision, initially led to a decrease of residual AHI to a low of 0.7, before progressively increasing to 15. A repeat PSG demonstrated severe OSA (AHI of 35), without evidence of CSA or nocturnal hypoventilation. ASV was resumed and patient's AHI progressively decreased to an average of 8, with improvement in his sleep apnea symptoms. Conclusion: SDM in CM patients can be explained by condition-related anatomical changes and depression of respiratory centers due to possible extrinsic compression leading to complex sleep apnea presentations. While it is unclear why this patient's sleep apnea improved then worsened after his latest decompression surgery, we believe that CSF recirculation and postoperative inflammation may be responsible. Close monitoring of SDB in patients with CM is important as they may require advanced therapies for proper control. Support (if any):